Reflections from a teachers’ perspective about the challenges faced by students with disabilities majoring in Japanese as a foreign language. - Hasegawa, H.; Nonis, Karen (International Journal of Special Education, 2018)
Learning to read and write the Japanese language is not an easy task. For the non-Japanese speaker this can be a struggle and a challenge. Some schools in Western Australia offer children the opportunity to learn Japanese as a foreign language. Consequently Japanese as a foreign language unit is offered to all undergraduate students in Education. All undergraduate students face challenges in mastering Japanese as a foreign language because of the stringent requirements of the language. It appears that the recognition and writing of Kanji (logogram) is one of the most challenging learning task for the learners. This paper is a reflective study based on the teacher’s perspective about University students’ challenges and problems in relation to writing and recognising Kanji. In this study, the teacher will reflect based on a framework of three questions. These questions include (1) The identification of the challenges and problems that university students with disabilities face in writing and recognising the Kanji script; (2) What are the adaptations that need to be considered in the delivery of the programme while retaining the integrity of the unit? (3) What changes should be made in the Assessment requirements to include the learning needs of students with disabilities?